Mimesis and Aesthetics of Drum Languages as a Cultural Artefact of Some Asafo Companies among the Oguaa People of Ghana - KQUOFI, STEVE; Sam, Johannes Atta; Glover, Reuben (Advances in Social Sciences Research Journal, 2015)
Drum languages as a cultural artefact is very pivotal in the Asafo system as far as their activities in the various communities are concerned. However, much documentation has not been done on the mimesis of the Asafo drum languages. Qualitative research methods were used to obtain all relevant data as well as accessing the knowledge and understanding of the drum languages from the prospective respondents. The research revealed that Asafo drums are a set of four but only one thus the Asafokyin (tuaakwan) is used to perform the all drum languages. Again, members of the various selected Asafo communities and even some members of the Asafo groups do have foreknowledge about Asafo drum languages but cannot interpret or comprehend some of the drum languages. Institutions like schools, radio and television stations and IT companies should be encouraged to use digitized drum languages as part of their system to enhance the fore knowledge and understanding of Asafo drum languages as a cultural artefact.